Caregiver burden from caring for dependent elderly in Yangon, The Republic of the Union of Myanmar - Naing, May Zun; May, Sein Yaw; Aung, Min Htike (UI Scholars Hub, 2020)
Background: Elderly population and well-being of those are emerging as major challenges for families and communities. This study aimed to identify caregiving burden among caregivers who care for dependent elderly. Methods: A cross sectional descriptive study was conducted in Tharkayta Township, Yangon, Myanmar. Total 200 caregivers were selected applying multi-stage sampling method and structured questionnaires were used to collect data. Dependent score of elderly was assessed by using Barthel Index of activities of daily living (ADL) and assessment of caregiver burden through Zarit Burden Interview. Results: The results showed that over one fifth of caregivers 21.5% had experienced severe burden, 39.5% had experienced moderate burden, 32.5% had experienced mild burden and only 6.5% had experienced no/little burden. Among elderly population, 11.5% were fully dependent, 40.0% were highly dependent, 46.0% were semi dependent, and only 2.5% were almost independent. Burden of caregivers and dependent score of elderly were negatively correlated (ß = ̶ 0.247, p = 0.000) and statistically significant association between age group and burden level (X2 = 17.335, p = 0.008). Conclusion: This study highlighted that community health nurses should emphasize on health education activities regarding caregivers training and home visit program for elderly and their caregivers.